Publisher Correction: Crocus-derived compounds alter the aggregation pathway of Alzheimer’s Disease - associated beta amyloid protein - Nikolaos Stavros Koulakiotis (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.